2008
DOI: 10.1021/ef800170j
|View full text |Cite
|
Sign up to set email alerts
|

Radicals from the Gas-Phase Pyrolysis of Hydroquinone: 1. Temperature Dependence of the Total Radical Yield

Abstract: The formation and temperature dependence of the total yields of radicals from the gas-phase pyrolysis of hydroquinone (HQ) over a temperature range of 350−950 °C was studied using the technique of low-temperature matrix isolation electron paramagnetic resonance (LTMI−EPR) spectroscopy. Annihilation procedures along with microwave power saturation studies of the frozen radicals as well as GC−MS analysis of products helped to clearly identify several types of radicals over the temperature range studied. On the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 26 publications
5
65
0
Order By: Relevance
“…The same trend was observed earlier in the gas-phase pyrolysis of hydro-quinone (HQ) at 550 to 750 °C and that of catechol (CT) at 600 to 750 °C, indicating the compositional changes of radicals at different temperatures. 45,46 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same trend was observed earlier in the gas-phase pyrolysis of hydro-quinone (HQ) at 550 to 750 °C and that of catechol (CT) at 600 to 750 °C, indicating the compositional changes of radicals at different temperatures. 45,46 …”
Section: Resultsmentioning
confidence: 99%
“…Variation of the g -value and Δ H p–p is indicative of either the existence of different types of radicals or of a significant disturbance in the matrix environment. 32 The signal intensity of a trapped radical is also an important characteristic parameter; it is calculated as the double integrated normalized intensity (DI/N) in WINEPR. This accounts for a number of variables, such as the conversion time, receiver gain and sweep width.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lomnicki et al [9] reported that p-hydroquinone gave p-benzoquinone in a 32% yield at 550 • C, while o-benzoquinone was not observed as a product from ohydroquinone (pyrocatechol). Such difference has been discussed with the influence of the position of hydroxyl group (p-or o-) on formation of semiquinone radicals as intermediates of benzoquinones [38,40,41].…”
Section: Gaseous Productsmentioning
confidence: 99%
“…Semiquinone radicals are known to be quite stable [12] and capable of reducing molecular oxygen to superoxide radical anion in a cyclic process [13]. Since monochlorinated phenoxyl radicals are valence isolectronic with semiquinone radicals and probably even more resistant to oxidation due to chlorine substitution, it is possible that chlorinated phenoxyl radicals may be even more toxic than the better studied semiquinone family of radicals.…”
Section: Introductionmentioning
confidence: 99%